PHARMACOLOGICAL PROPERTIES OF THE SUBSTANCE HEPARIN (Academicia Globe: Inderscience Research, 2023)
Heparin is used to prevent blood clots from forming in people who have certain medical conditions or who are undergoing certain medical procedures that increase the chance that clots will form. Heparin is also used to stop the growth of clots that have already formed in the blood vessels, but it cannot be used to decrease the size of clots that have already formed. Heparin is also used in small amounts to prevent blood clots from forming in catheters (small plastic tubes through which medication can be administered or blood drawn) that are left in veins over a period of time. Heparin is in a class of medications called anticoagulants ('blood thinners'). It works by decreasing the clotting ability of the blood.